Coinage metal complexes of multidentate Pacman phosphane ligands. Issue 35 (12th April 2023) - Ohms, Leon; Eickhoff, Liesa; Kramer, Pascal; Villinger, Alexander; Bresien, Jonas; Schulz, Axel
Abstract : A new way to play "Pac-Man™": We have synthesized two different Pacman phosphanes as a new kind of multidentate phosphane ligands and used them to complex coinage metals. Abstract : We present the extension of Pacman ligands to bidentate phosphane ligands enabling them to bind metals in their sterically protected cavity. The coordination of coinage metals shows the ability of the ligand to adopt different coordination modes by distortion, of which some additionally include the imine nitrogen atoms. Besides the coordinated metal, the substitution on the phosphorus atoms influences the type of coordination.